2005
DOI: 10.1007/s11249-004-2755-6
|View full text |Cite
|
Sign up to set email alerts
|

Pumping effect of sliders in hard disk systems

Abstract: The accumulation of contaminants on the slider surface is of paramount importance in hard disk drives because only an ultra small amount of contaminants on the slider surface will cause catastrophic failures for hard disk drives with a spacing between the slider and the hard disk as small as 10 nm, which will be reduced further in the near future to about 5-6 nm in order to attain a recording density of 100 Gbit/in 2 . In this paper the pumping effect of the slider is proposed as one mechanism of the contamina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2005
2005
2012
2012

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 13 publications
(28 reference statements)
0
3
0
Order By: Relevance
“…Previous studies have shown that lubricant originally coated on the disk can be transferred to the slider surface through various mechanisms such as evaporation-condensation, migration, electrostatic attractions, and direct pickup due to intermittent contacts [2][3][4][5][6]. The accumulation of lubricant on the ABS has been a serious problem affecting hard disk drive reliability.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that lubricant originally coated on the disk can be transferred to the slider surface through various mechanisms such as evaporation-condensation, migration, electrostatic attractions, and direct pickup due to intermittent contacts [2][3][4][5][6]. The accumulation of lubricant on the ABS has been a serious problem affecting hard disk drive reliability.…”
Section: Introductionmentioning
confidence: 99%
“…2 the recording slider-to-media spacing must approach 2 -3 nm. 4,5 In a previous study we have reported that the dielectric nature of media overcoats have a significant effect on the van der Waals interaction between the head and the disk. Media overcoats are large contributors to this spacing and will have to be minimized in order to attain 2 -3 nm.…”
mentioning
confidence: 99%
“…In earlier models A͑L͒ was taken as a constant with a typical value ϳ10 −19 J. 5 Starting with the simplest case, the Hamaker function A 132 ͑L͒ of substrate 1 interacting with substrate 2 across thickness L of medium 3 ͓see Fig. 1͑b͔͒.…”
mentioning
confidence: 99%